Interactive sound art and animated notation as an ensemble performance platform in primary level music education - Lind, Anders (Educare, 2020)
This article showcases excerpts of my artistic research in progress. In particular, I demonstrate how an interdisciplinary approach combining knowledge from the fields of artistic research, Human Computer Interaction (HCI) and game studies mayinspire primary level music education of today. I highlight examples of novel digital music technology and present an innovate approach to using these for group performance exercises in the music classroom. In particular, I report from a study where my interactive sound art exhibition LINES, in combination with animated music notation, was used as a digital ensemble music platform. The data of the study comprises five workshop sessions with pre-schoolers using this platform. An autoethnographic method and analysis of video documentation of the workshop sessions were used as methods for the study. The results showed that LINES was both engaging and easily accessed. Moreover, it allowed the majority of the target group to perform musical exercises as an ensemble. I argue that the use of traditional instruments and traditional notation creates a democratic issue in primary level music education. Furthermore, with support from the study and related research, I argue that platforms such as this may democratize music education involving pupils aged 5-15 years.